The pitfalls of central clearing in the presence of systematic risk - Christian Kubitza; Loriana Pelizzon; Mila Getmansky (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2018)
Through the lens of market participants' objective to minimize counterparty risk, we provide an explanation for the reluctance to clear derivative trades in the absence of a central clearing obligation. We develop a comprehensive understanding of the benefits and potential pitfalls with respect to a single market participant's counterparty risk exposure when moving from a bilateral to a clearing architecture for derivative markets. Previous studies suggest that central clearing is beneficial for single market participants in the presence of a sufficiently large number of clearing members. We show that three elements can render central clearing harmful for a market participant's counterparty risk exposure regardless of the number of its counterparties: 1) correlation across and within derivative classes (i.e., systematic risk), 2) collateralization of derivative claims, and 3) loss sharing among clearing members. Our results have substantial implications for the design of derivatives markets, and highlight that recent central clearing reforms might not incentivize market participants to clear derivatives.
Keywords: G01; G14; G18; G28; 330; Central Clearing; Counterparty Risk; Systematic Risk; OTC markets; Derivatives; Loss Sharing; Collateral; Margin